2014
DOI: 10.3109/10717544.2014.910565
|View full text |Cite
|
Sign up to set email alerts
|

Microdialysis pharmacokinetic study of scopolamine in plasma, olfactory bulb and vestibule after intranasal administration

Abstract: The purpose of this study was to investigate the microdialysis pharmacokinetic of scopolamine in plasma, olfactory bulb and vestibule after intranasal administration. The pharmacokinetic study of subcutaneous and oral administration was also performed in rats. From the in vivo results, scopolamine intranasal administration can avoid hepatic first-pass effect. T max plasma samples after intranasal administration were significantly faster than oral administration and subcutaneous injection. The relative bioavail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Intranasal administration has been established as an effective method for drug delivery to the brain 59 via the olfactory system 60 . These studies suggest that intranasally applied ketamine enters the brain through the olfactory system, where the olfactory nerves traverse holes in the cribiform plate into the olfactory bulb, which sits immediately below the vmPFC (Figure 1).…”
Section: Intranasal Ketamine Is Ideally Positioned To Target Higher Pmentioning
confidence: 99%
“…Intranasal administration has been established as an effective method for drug delivery to the brain 59 via the olfactory system 60 . These studies suggest that intranasally applied ketamine enters the brain through the olfactory system, where the olfactory nerves traverse holes in the cribiform plate into the olfactory bulb, which sits immediately below the vmPFC (Figure 1).…”
Section: Intranasal Ketamine Is Ideally Positioned To Target Higher Pmentioning
confidence: 99%
“…Intranasal orexin‐A delivery has been reported to be more effective than intravenous administration in terms of receptor binding in mouse brain (Hanson et al, 2004). Pharmacokinetics studies showed that intranasal scopolamine resulted in a rapid increase in plasma drug concentration for both animals and humans (Stankovic et al, 2019; Wei et al, 2016). In contrast, intranasal delivery of orexin‐A rapidly targets the brain with limited blood distribution (Dhuria et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…For intranasal administration in cats, scopolamine, a nonselective competitive muscarinic receptor antagonist, was utilized as a positive control drug in nasal spray form (Klocker et al, 2001; Wei et al, 2016). Scopolamine and orexin‐A were dissolved in 0.9% saline solution and sterile water with the final concentration at 4 and 20 μg·μl −1 , respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…While we achieved a similar effect on choice behavior (Figure 2A, 3A), as well as similar plasma concentrations (Figure S8) with a 1 mg/kg IN dose and a 0.5 mg/kg IM dose, an efficacy difference which is likely explained by a difference in bioavailability (Malinovsky et al, 1996; Yanagihara et al, 2003), we observed a marked reduction in ketamine’s side effects on mayor eye movement measures (Figure 5). IN administered ketamine is thought to reach the brain via the olfactory system, through holes in the cribriform plate where the olfactory nerve enters the brain (Patel et al, 2016; Wei et al, 2016), which in turn sits directly below the prefrontal cortex. When used as an antidepressant, this may allow IN administered ketamine to directly reach brain regions where it may have its therapeutic actions.…”
Section: Discussionmentioning
confidence: 99%